2020
DOI: 10.21203/rs.3.rs-15621/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of Primary Headache Disorders among Information Technology Staff in China: The Negative Effects of Computer Use and Other Correlative Factors

Abstract: Background To date, there have been very few studies that have explored the relationship between headaches and computer use. The chief aim of this study is to investigate the prevalence of primary headache disorders among informational technology staff and identify the potential factors contributing to it. Methods This is a cross-sectional study based on annual health checks of employees from the information technology industry. We identified 2216 information technology staff members from Beijing by stratif… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
1
0
1
Order By: Relevance
“…Different from Li et al study who's stated that there was a relationship between duration of computer usage with the incidence of primary headaches especially TTH. There are differences in the groups of subjects studied wherein the study of Li et al identified IT employees where the majority of them were in front of a laptop or computer monitor for more than 8 h [21]. American Optometric Association recommends following the 20-20-20 rules to alleviate digital eyestrain, which is every 20 min staring at the monitor screen, we should rest our eyes for 20 s by looking at something 20 feet away [22].…”
Section: Resultsmentioning
confidence: 99%
“…Different from Li et al study who's stated that there was a relationship between duration of computer usage with the incidence of primary headaches especially TTH. There are differences in the groups of subjects studied wherein the study of Li et al identified IT employees where the majority of them were in front of a laptop or computer monitor for more than 8 h [21]. American Optometric Association recommends following the 20-20-20 rules to alleviate digital eyestrain, which is every 20 min staring at the monitor screen, we should rest our eyes for 20 s by looking at something 20 feet away [22].…”
Section: Resultsmentioning
confidence: 99%
“…El uso de PVD es otro de los aspectos contemplados en los estudios realizados con las cefaleas primarias (21) , mostrando coincidencia con los resultados obtenidos en nuestro trabajo respecto a la percepción de los pacientes en cuanto a su impacto en la migraña. La aparición de migraña se relaciona en múltiples publicaciones con actividades y condiciones laborales y de estilo de vida variadas, pero sin que pueda establecerse una clara relación causa-efecto con la severidad o frecuencia de la enfermedad.…”
Section: Discussionunclassified